Pengaruh Hasil Belajar Pendidikan Pancasila Kelas IV Melalui Model Problem Based Learning Berbantuan Media Utagory SD 2 Jepang. - Ranti Wahyuni; Sri Utaminingsih; Imaniar Purbasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
A study conducted at SD 2 Jepang focused on improving elementary school students' learning outcomes in Pancasila Education by implementing the Problem- Based Learning model assisted by utagory media. The research aimed to address issues including lack of student interest, low classroom engagement, monotonous lectures, and limited learning media. The research followed a quantitative experimental model, using a one-group pretest posttest design with a sample size of 25 students. Various data collection techniques were employed, such as tests, interviews, observations, and documentation. The findings revealed a significant improvement in student learning outcomes, with an average pretest score of 48.2 and an average posttest score of 77. The hypothesis testing confirmed the impact of the Problem-Based Learning model assisted by utagory media, as indicated by a significance value (2-tailed) of 0.000, confirming that Ha is accepted and Ho is rejected. Thus, the study demonstrated that the application of this learning model positively influenced Pancasila Education in the fourth-grade class at SD 2 Jepang.